Impact Des Feuilletons Turcs Sur Le Telespectateur Arabe : Cas De Maroc Et Yemen - Basheer, Zendal; Abdelkader, Gonegai (European Scientific Journal, ESJ, 2016)
This work aims to find out the impact of Turkish soap operas on Arab viewer in two different populations in the political and economic situation such as Morocco and Yemen, a survey is conducted on two universities: the University Hassan II in Morocco with about 151 students (48.40%) and the University of Sanaa in Yemen with 161 students (51.60%). The results of the survey showed that participants spend hours watching TV (over 3 hours) to 4.5% (depending on circumstances) to 57.1%. The lack of good Arabic drama is the main reason to watch Turkish soap operas for more than (79%) following the presentation of interesting and attractive subjects as for more than (79%), romantic themes, the performance of Turkish actors , the sets were remarkably beautiful (80%), physical beauty of the actors (70%), the attractiveness of the filming locations (88.14%) and dubbing in Arabic especially in Syrian dialect (57%). The study concluded the impact of Turkish soap operas on the Arab viewer by Turkish fashion (almost 60%) following by the beautiful nature of Turkey (more than 78%), put the ringtone of a Turkish song (45%). Most of the sample who thought of the acquisition of weapons as in the Turkish soap operas are from Yemen (80% Yemeni and 20% Moroccan) and dream to travel to Turkey is hoping to (more than 94%).